2010
DOI: 10.1016/j.ijcard.2009.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of stroke in chronic heart failure patients with normal sinus rhythm: Findings from the DIG stroke sub-study

Abstract: Background-Little is known about the epidemiology of stroke in chronic systolic and diastolic heart failure (HF) patients in normal sinus rhythm (NSR) receiving angiotensin-converting enzyme (ACE) inhibitors. Because all HF patients in the Digitalis Investigation Group (DIG) trial (N=7788) were in NSR and nearly all were receiving ACE inhibitors, a survey-based stroke substudy was conducted but its findings have never been published.Methods-DIG investigators confirmed a total 222 cases of stroke of which 144 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…The studies support consideration of the CHA 2 DS 2 -VASc score for prediction of the risk of stroke in HF irrespective of AF presence. Indeed, several studies examined the components of the CHA 2 DS 2 -VASc score and demonstrated their individual association with stroke in HF: congestive HF represented by a decreased ejection fraction (hazard ratio [HR] 0.98–2.15) [ 15 •, 34 , 62 , 63 ], hypertension (HR 1.18) [ 15 •, 62 , 64 , 65 ], age (HR 1.34–1.35) [ 14 , 15 •, 62 64 ], diabetes mellitus (HR 1.114–1.87) [ 14 , 15 •, 16 ••, 62 , 63 , 65 ], prior stroke/TIA (HR 1.81–2.68) [ 14 , 15 •, 39 , 63 , 64 ], vascular disease (HR 1.34) [ 66 ], and gender (HR 0.569) [ 15 •, 62 , 63 ]. In WARCEF sub-study with patients with sinus rhythm, the ejection fraction was associated with stroke only if its baseline values were less than 15% [ 62 , 63 ].…”
Section: Risk Stratification Of Stroke In Hfmentioning
confidence: 99%
“…The studies support consideration of the CHA 2 DS 2 -VASc score for prediction of the risk of stroke in HF irrespective of AF presence. Indeed, several studies examined the components of the CHA 2 DS 2 -VASc score and demonstrated their individual association with stroke in HF: congestive HF represented by a decreased ejection fraction (hazard ratio [HR] 0.98–2.15) [ 15 •, 34 , 62 , 63 ], hypertension (HR 1.18) [ 15 •, 62 , 64 , 65 ], age (HR 1.34–1.35) [ 14 , 15 •, 62 64 ], diabetes mellitus (HR 1.114–1.87) [ 14 , 15 •, 16 ••, 62 , 63 , 65 ], prior stroke/TIA (HR 1.81–2.68) [ 14 , 15 •, 39 , 63 , 64 ], vascular disease (HR 1.34) [ 66 ], and gender (HR 0.569) [ 15 •, 62 , 63 ]. In WARCEF sub-study with patients with sinus rhythm, the ejection fraction was associated with stroke only if its baseline values were less than 15% [ 62 , 63 ].…”
Section: Risk Stratification Of Stroke In Hfmentioning
confidence: 99%
“…Hypertension was not a risk factor for stroke in a study of patients with left ventricular systolic dysfunction,9 and in Studies of Left Ventricular Dysfunction, hypertension imparted a small relative risk of stroke only in men (RR 1.32 95%CI: 1.04-1.69; p=0.02) but no significant risk in women 10. Two recent sub-studies of the Digitalis Investigation Group trial11, 12 however, showed a history of hypertension to be an independent predictor of stroke (adjusted odds ratio 1.46; 95% CI:1.11-1.94)12 and a risk factor for hospitalization for stroke (hazard ratio 1.52; 95%CI:1.11-2.08) among patients with HF.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, one community based study reported a 17.4 fold increase risk of ischemic stroke within the first month after heart failure diagnosis [7]. However, the Digitalis Investigation Group stroke substudy found an annual stroke risk of only 1% [8].…”
Section: Introductionmentioning
confidence: 99%